(untitled) (Journal of Science, Technology and Innovation Policy, 2021)
Managing hazardous waste is a challenging and demanding task, especially in terms of its implementation and monitoring. Malaysia has had policies and regulations on the management of hazardous wastes for the past 30 years and it is constantly in need of improvement and renewal in line with the changing times and technologies involved in producing these hazardous wastes. This study is related to the proposal to improve policies and regulations related to hazardous waste especially to household hazardous waste. The study begins by looking at previously implemented policies and related issues as well as paving the way for developing a new policy and regulations to address the challenges associated with hazardous waste that do not yet have policies and regulations in place. Qualitative research was conducted by examining previous documents related to hazardous waste, interviews, surveys and group discussions held in workshops and seminars related to this topic. All the data and information obtained is carefully analyzed and formulated to serve as a guide to formulate policies and regulations regarding hazardous waste in the future for Malaysia.